The influence of electronic word of mouth (ewom) on the purchase intention of technological gadgets - Tiew, Keh Yeng (2023)
Electronic word-of-mouth (eWOM) can be defined as any positive or negative opinion or comment that is created by potential, actual, or past users about a good or a company via the internet. The main objective of this study is to identify key factors affecting the purchase intention of technological gadgets in Malaysia. Concerning this, the factors that will investigate in this study are information quality, information quantity, information credibility, information adoption, perceived usefulness, using experience of eWOM. The underlying theories of this study are the Information Adoption Model (IAM), the Technology Acceptance Model (TAM), and the Theory of Planned Behavior (TPB). The targeted population is the consumer who stayed in Malaysia that have past or current experience in reading online reviews about technological gadgets. The age range targeted is between 18 to 50 years old. By using the convenience sampling method, 242 valid survey responses were utilized in this study. The findings indicated that Malaysian consumers have chosen YouTube to be the most frequently used social media platform for studying online reviews about technological gadgets. Also, the results indicated information quantity, information adoption, perceived usefulness, and using experience of eWOM would be the factors influencing the purchase intention of technological gadgets. Nevertheless, this research provides valuable implications to the marketers to focus on delivering eWOM as the marketing tool to make further improvements towards digital marketing in Malaysia. Lastly, limitations and recommendations have been illustrated for future researchers to improve while researching similar studies.